Student perceptions on the integration of sustainability in Teaching Social Studies - Samuel Balbin; Faith Micah A Balbin (Universidade Estadual de Alagoas, 2024)
This study delves into how social studies teachers integrate sustainability principles into their daily teaching practices in the lens of the student. Employing a mixed-method approach, the research combines a descriptive survey (n=28) with follow-up interviews (n=10) of third-year social studies students at Rizal Technological University in the Philippines. Utilizing the Statistical Package for the Social Sciences (SPSS), quantitative data were analyzed to gauge the extent of sustainability integration, while qualitative data, obtained through semi-structured interviews, delved into student perceptions of teachers' strategies, challenges, and overall effectiveness. The findings reveal that students recognize the inclusion of sustainability concepts in their social studies education, yet the depth and consistency of this integration appear uneven. Thematic analysis of interview data unveiled specific strategies employed by teachers, such as incorporating real-life examples and project-based learning, while students highlighted challenges such as limited resources and curriculum constraints. Moreover, student feedback underscored the value of engaging approaches and the need for more consistent application of sustainability principles across the curriculum. Based on these findings, the study recommends fostering stronger partnerships with local communities to bridge the theory-practice gap in sustainability education, thereby providing valuable resources, guest speakers, and real-world project opportunities for students, empowering them to actively contribute to building a sustainable future.